Pengaruh Gaya Belajar Terhadap Prestasi Mahasiswa Universitas Djuanda - Nazirah Naswa (Yayasan Pengembangan Dan Pemberdayaan Nusantara, 2026)
Learning styles are one of the internal factors that influence students’ academic achievement. Each individual has a unique way of absorbing and processing information, which affects the effectiveness of the learning process. This study aims to examine the influence of learning styles on the academic achievement of students at Djuanda University. The research employed a quantitative correlational method with a simple random sampling technique involving 33 student respondents. Data were collected through questionnaires, observations, and documentation, and analyzed using SPSS version 25 through validity and reliability tests, Pearson correlation, simple linear regression analysis, coefficient of determination, and ANOVA test. The results indicate a positive and significant relationship between learning styles and students’ academic achievement, with a correlation coefficient (R) of 0.938 and a coefficient of determination (R Square) of 0.880. This finding suggests that 88% of the variation in students’ academic achievement is explained by learning styles, while the remaining 12% is influenced by other factors outside this study. The ANOVA test produced an F value of 19.886 with a significance value of < 0.001 (< 0.05), indicating that the regression model is feasible. Partially, indicator X1.8 has a significant effect on students’ academic achievement with a significance value of 0.047. Therefore, it can be concluded that the better the learning style applied by students, the higher their academic achievement. These findings highlight the importance of understanding individual learning styles as a basis for developing effective learning strategies in higher education.